A study on service quality in relations towards customer satisfaction among express bus customer in Kuantan - Nor Fillianie, Aziz (2013)
This study is an overview of the service quality and customer satisfaction among express bus customer in Kuantan, Pahang. The aim is also to get feedback on the user's perception of quality express bus service provided and the level of satisfaction with the service. Besides that this survey is designed to measure the quality of existing services and improvements. Therefore, to identify the problems related to survey with 200 respondents in Pahang was conducted to obtain information about problems that occur. The location of the research will be conduct at Kuantan Central Terminals. It is because the location very suitable to get information about the bus service and many person at that location. Some of the method the research use to get problem statement is from respondent conversation. That response stated that consumers who use express bus service for their travel experience problems dissatisfaction. This is because the factors affecting the service quality and management provided by the service. This situation has attracted researcher to conduct a study on service quality in relations towards customer satisfaction among express bus customer in Kuantan. This review will focus on several dimensions of service quality and customer satisfaction means to measure and evaluate the service quality of the relationship. At the end of the study, the researchers propose some suggestions that the authorities concerned are more responsible for improving the quality of express bus service so that users get the convenience to use public transport. This study will be evaluated and analyzed to obtain the results. Further, this study will be conducted and the data selected at the 15-19 November 2013. After that researcher analyze the data to SPSS software. Then the data show that have significant relationship between service quality (assurance, tangibles, reliability, and responsiveness) with customers satisfaction. While the researcher writes the report and all of the research can be use for the reference and next researcher.